RNA extraction, probe preparation, and competitive hybridization for transcriptional profiling using Neurospora crassa long-oligomer DNA microarrays - Travis A. Clark; Julie M. Guilmette; Daniel Renstrom; Jeffrey P. Townsend (Fungal Genetics Reports, 2008)
We developed protocols optimized for the performance of experiments assaying genomic gene expression using Neurospora crassa long-oligomer microarrays. We present methods for sample growth and harvesting, total RNA extraction, poly(A)+ mRNA selection, preparation of NH3-Allyl Cy3/Cy5 labeled probes, and microarray hybridization. The quality of the data obtained with these protocols is demonstrated by the comparative transcriptional profiling of basal and apical zones of vegetative growth of N. crassa.